2021
DOI: 10.1007/s11214-021-00857-0
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding the Origins of Problem Geomagnetic Storms Associated with “Stealth” Coronal Mass Ejections

Abstract: Geomagnetic storms are an important aspect of space weather and can result in significant impacts on space- and ground-based assets. The majority of strong storms are associated with the passage of interplanetary coronal mass ejections (ICMEs) in the near-Earth environment. In many cases, these ICMEs can be traced back unambiguously to a specific coronal mass ejection (CME) and solar activity on the frontside of the Sun. Hence, predicting the arrival of ICMEs at Earth from routine observations of CMEs and sola… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 174 publications
0
29
0
Order By: Relevance
“…This results in a type of base-difference image sequence where the (averaged) difference Ĩproc is above the intensity minimum values over a temporal interval rather than from the intensity at an initial time. In general, base-difference processing has demonstrated an advantage in the identification of larger-scale, slowly-varying signatures of eruptive transients, such as the EUV dimmings and/or brightenings, associated with stealth or stealthy CME eruptions (e.g., Palmerio et al, 2021b;Nitta et al, 2021).…”
Section: Stereo-a/cor1 Image Processing and Height-time Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in a type of base-difference image sequence where the (averaged) difference Ĩproc is above the intensity minimum values over a temporal interval rather than from the intensity at an initial time. In general, base-difference processing has demonstrated an advantage in the identification of larger-scale, slowly-varying signatures of eruptive transients, such as the EUV dimmings and/or brightenings, associated with stealth or stealthy CME eruptions (e.g., Palmerio et al, 2021b;Nitta et al, 2021).…”
Section: Stereo-a/cor1 Image Processing and Height-time Profilesmentioning
confidence: 99%
“…Recent high-resolution, multi-wavelength, and multi-viewpoint coronal observations have revealed weak low-coronal dynamics associated with stealth CMEs, in some cases enabling study of their formation and lift-off (Korreck et al, 2020;O'Kane et al, 2021;Palmerio et al, 2021b). Stealth CMEs may also cause significant magnetic storms at Earth that are problematic for space weather forecasting (Nitta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Robbrecht et al (2009b) concluded that one reason why these ejections do not present clear source signatures is their large lift-off heights, usually above 1.4 solar radii (R ). Even though their sources are dif-ficult to locate, stealth CMEs can be unexpectedly geoeffective (Kilpua et al 2014;Liu et al 2016;Nitta et al 2021). One reason is that the magnetic fields of slow and stealth CMEs may be enhanced by interactions with the background solar wind through which they are propagating, resulting in surprisingly strong geomagnetic storms (He et al 2018;Chen et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The mutual connections of the environmental processes are well-known. They have been carefully investigated in the past and are under investigation now [31][32][33][34][35][36][37][38][39][40][41][42]. It is well-known that the particle fluxes behavior in the inter-planet space, and particularly in Earth's vicinity, named the near-Earth space or Geospace [31,32] in the radiation belts, is governed by solar wind [31].…”
Section: Introductionmentioning
confidence: 99%
“…As the result, the density and speed of different particles in the radiation belts vary in a wide range that affects the magnetosphere and ionosphere status. Additionally, the separate events-solar coronal mass ejection (CME)-can affect the magnetosphere [33]. The magnetosphere-ionosphere interactions [34,35] give additional complexity to the cosmic impact on the Earth.…”
Section: Introductionmentioning
confidence: 99%